Interpretation of lung cancer study outcomes - Cortinovis, Diego; Abbate, Marida; Bidoli, Paolo; Pelizzoni, Davide; Canova, Stefania (Journal of Thoracic Disease; Vol 7, No 11 (November 28, 2015): Journal of Thoracic Disease, 2015)
Lung cancer is the leading cause of cancer death in developed countries. However, in the last few years we observed an important acceleration in drug development due to oncogenic driver tumors discovery. Sharing and putting together preclinical data from benchmark and data from clinical research is the scientific paradigm that allows real breakthrough in clinical practice in this field, but only a few targeted agents are worthy and practice changing. The clinical research and proper use of statistical methodology are the pillars to continue to achieve important goals like improvement of overall survival. A good medical oncologist should be able to critically read a scientific paper and move from the observed outcomes into clinical perspective. Despite clinical improvements, sometimes the union of promising targeted agents and optimistic expectations misrepresent the reality and the value of clinical research. In this article, we try to analyze the meaning of statistical assumptions from clinical trials, especially in lung cancer, through a critical review of the concept of value-based medicine. We also attempt to give the reader some practical tools to weigh scientific value of literature reports.